Influência da deformação a frio na microestrutura, propriedades mecânicas e magnéticas, textura e corrosão por pites de aços AISI 301LN e 316L - Silva, Paulo Maria de Oliveira (2005)
Austenitic stainless steels (ASS) are widely used in food, transportation, nuclear and petrochemical industries because of their excellent combination of mechanical strength, formability and corrosion resistance. Among these grades, AISI 301 outstands due to its superior mechanical strength. However, this steel has the weakest corrosion resistance. The corrosion resistance of ASS is based on its passive film enriched in Cr203 that can be easily destroyed in chloride-rich environments. The aim of this work was to study the effect of cold rolling on the microstructure and properties of AISI 301LN and 316 stainless steels. The selection of AISI 301LN for the frame of rail cars to be used in Fortaleza subway system justifies its choice to be investigated knowing that the city is situated in a very chloride-rich environment. X-ray diffraction, quantitative metallography, optical microscopy, scanning electron microscopy, and atomic force microscopy were employed to characterize materials microstructure; x-ray crystallographjc texture, magnetic measurements, microhardness and immersion test into FeCl3 6H2O were used in order to evaluate materials performance against pitting corrosion. Cold work caused α’ martensite formation and austenite strain hardening which were responsible for loss of corrosion resistance in both steels. By evaluation of crystallographic texture, it arises an indication for the transformation austenite-ferrite to have followed KURDJUMOV-SACHS orientation relationship.